Effects Of Non-Existent Ear, Nose, And Throat Clinics On Residents Seeking Health Care At Adankwame Health Centre In Ashanti Region, Ghana - Opoku Agyemang, Cecilia; Opoku, Oscar Agyemang; Maamle Osragbo, Rebecca; Alhassan, Ubaidatu; Nyarko Mensah, Olivia; Opoku, Albert (Journal of Applied Nursing and Health, 2024)
Background: Ear, Nose, and Throat (ENT) problems such as the common cold, Otitis Media, and Tonsillitis are standard worldwide and remain a global burden. Bringing ENT services closer to the community remains a key component of reducing the burden of ENT conditions across low and middle-income countries such as Ghana. Yet a shortage of special ENT clinics and specialists to manage these conditions remains. In light of this, the study aimed to assess the effects of non-existent ENT clinics on residents seeking health care at Adankwame Health Center in the Atwima Nwabiagya North District. Methods: A descriptive cross-sectional survey design was used, using a quantitative approach. The population for the study included residents above 15 years who had visited Adankwame Health Center during the study period. With the convenience sampling technique, 100 respondents were selected for the study. Data was collected with a well-structured questionnaire after an ethical clearance had been sought from the Institutional Review Committee. The data collected was analyzed in frequency tables, pie charts, and graphs using Microsoft Excel 2020 data analysis software and the Statistical Package for Social Sciences (SPSS) 25.0 Results: The study concluded that general knowledge and awareness of the ENT clinic were high among residents who attended Adankwame Health Centre. Some physiological effects identified were hearing impairments, chronic ENT conditions, and delayed speech. Parental depression, probably due to children suffering from delayed speech and language, was the psychological effect identified in this study. Conclusion: The financial burden was seen in all aspects, as respondents complained of the high cost of transportation when seeking ENT care from secondary and tertiary facilities outside the Adankwame community. The Health Directorate of Atwima Nwabiagya North District should prioritize extending the establishment of ENT clinics in rural areas.